Nokona / Nur Fatin Nadirah Ismadi - Ismadi, Nur Fatin Nadirah (Universiti Teknologi MARA, Kedah, 2025)
NoKono is o locol made chocolote bor variety of flavours produce in Jitra. Kedah. NoKono established since December 2020 by Puan Aishah Binti Azizan. NoKono ~ a word form Japanese which mean rich and healthy but in Kedoh slang the pronunciation is 'no k.ono-kona which mean don't make tum. This company have been produce a lot of chocolate product. Their vision is to make the company become famous as tourism place. The most important is NoKona product is certified Halal Jokim. NoKono Coldot Bar is offers on impressive selection of t 2 unique flavours that crafted to cater to a wide range of taste preferences. NoKono Coldat Bar includes delightful option for fruit lovers like apple, orange, berry and strawberry that providing a refreshing burst of natural sweetness. Other then that. NoKono also indulge in classic favourites such as milk chocolate. dork chocolate, milk chocolate and along with the rich and aromatic coffee flavour fir a caffeine-inspired treat. For those seeking something more adventurous and unique taste. NoKona Coklat Bar introduces distinctive flavours like green tea. salted egg, sak:uro and butterscotch to ensuring there is something special for everyone to enjoy. Whether your prefer familiar tastes or enjoy exploring unconventional flavour combinations, NoKono Coldot Bar offers a truly divers and satisfying chocolate experience. The packaging design for NoKono Coklot Bar incorporates iconic landmarks from Kedah as a central element. blending them seamlessly with themes of fun and fan tasy. This imaginative design approach reflects the playful nature of chocolate and creates a visually engaging experience for consumers. Bright and striking coloo are used to ensure the packaging stands out on shelves, instantly catching the eye and enticing potential buyers. The decision to feoture Kedoh landmarks is particularly significant. as 2025 hos been designated as the 'Visit Kedoh Year." By showcasing these iconic sites, the packaging not only promotes the unique cultural and natural beauty of Kedoh but also aligns with the brooder effort to boost tourism in the region. This creative synergy between the chocolate's design and the promotional campaign transforms NoKono Coklot Bar into more than just a treat it becomes a delightful ambassador for Kedoh, sparking curiosity and encouraging exploration of the stole. This innovative packaging design successfully combines local pride, fantasy, and visual appeal to create a product that is both meaningful and marketable. NoKono hos introduced on adorable and lovable bunny as its official mascot. a choice that reflects the brand's core values and its desire lo create a connection with consume~ of all ages. The bunny symbolizes agility. nimbleness, and cleanliness, trails that resonate with the brand's commitment to delivering high-quality and thoughtfully crafted chocolate products. Its energetic and playful nature mirrors the excitement and joy that NoKono aims to bring to every bite of its chocolate bo~. Bunnies ore unive~olly regarded as gentle and approachable creatures, making them especially appealing to children. Its soft, cuddly appearance sparks feelings of happiness and warmth, making it on ideal character to represent the fun and fantasy associated with NoKono chocolates. For parents, the bunny mascot reinforces the idea that NoKono products ore not only delicious but also wholesome and family-friendly.